ABUNDANCE AND DIVERSITY OF COLLEMBOLA INSECTS IN SWITCHING FIELDS IN WAAI VILLAGE CENTRAL MALUKU - Suriani, Sanita; Tuasella, Frisca N; Moniharapon, Mechiavel (Universitas Pattimura, 2021)
Collembola are a good example of the diversity of soil animals and play an important role in nutrient cycling, organic matter decomposition and soil formation which are important parts of forest ecosystems. This research was conducted on cassava land and a vegetable garden in Waai village, Salahutu sub-district, Central Maluku district, on July 18 2020. This study aims to determine the abundance and diversity of the Collembola insect in shifting cultivation in Waai village, Salahutu sub-district, Central Maluku district and its relationship with environmental factors. Results The study obtained 3 families and 6 species with a total abundance of 12.2 individuals/m2. There are differences in the abundance of Collembola found in vegetable gardens and cassava fields. The abundance of Collembola found in the vegetable garden was 3.6 individuals consisting of 2 families and 2 species, while in cassava fields it was 8.6 individuals divided into 2 families and 4 species.